Mineral Deposit Research: Meeting the Global Challenge: Proceedings of the Eighth Biennial SGA Meeting Beijing, China, 18 - 21 August 2005 - Mao, Jingwen (Springer Berlin Heidelberg, 2005)
The proceedings volume is a compilation of approximately 400 extended abstracts (up to 4 pages long) of presentations given at the 8th Biennial SGA Meeting. The papers are grouped according to the thematic sessions within which they were presented, including Tectonics, lithospheric, and deep mantle controls on global metallogenic provinces and giant ore deposits, Base and precious metal mineralization in sediments during basin evolution, Metallogeny and exploration of uranium deposits, Magmas and base-metal ore deposits, Epigenetic gold systems, Submarine ore systems and ancient analogues, Understanding ore systems though precise geochronology, isotope tracing and microgeochemistry, Geology and economics of non-metallic resources, Conceptual targeting of mineral deposits. Due to the meeting being held in Beijing, the conference and proceedings volume also feature thematic sessions that focus on specific regions throughout Asia, such as Mesozoic to recent geodynamics and metallogeny of eastern Asia, Metallogeny of the Tethys-Himalayan Orogen, Geodynamics and metallogeny of the Altaid Orogen, and Exploration, Discovery, and Mine Developments in China. As such, the volume represents a comprehensive summary of cutting-edge developments across a wide range of subject matters that are of extreme relevance to the global research, mining and exploration community.
Keywords: Konferenzschrift